Separation of Bumn Losses Affects the Legal Liability of the Board of Directors - Adinda Rindang Kasih Adinda (Lambung Mangkurat Law Journal, 2026)
The separation between state-owned enterprises’ (BUMN) business losses and state financial losses constitutes a crucial issue in Indonesian corporate law. Historically, losses incurred by BUMN were often equated with state losses, creating legal uncertainty and exposing directors to potential criminal liability under the Anti-Corruption Law (UU Tipikor). This research employs a normative legal method with a library research approach to analyze the juridical implications of distinguishing corporate losses from state losses and its impact on directors’ legal accountability. The findings highlight that the latest BUMN Law (Law No. 1 of 2025) explicitly positions BUMN as private legal entities in the form of limited liability companies, thus clarifying that business losses should primarily be regarded as corporate losses. Consequently, directors’ responsibilities must be assessed based on corporate governance principles fiduciary duty, duty of care, and the business judgment rule rather than automatically through criminal sanctions. Furthermore, notaries play a pivotal role in documenting directors’ decisions through authentic deeds, serving as preventive instruments to ensure legal certainty, distinguish lawful business risks from unlawful acts, and protect directors from disproportionate criminalization. The separation of BUMN and state losses ultimately strengthens corporate accountability, fosters a healthier investment climate, and enhances the legitimacy of notarial practice in supporting professional corporate governance in Indonesia.